Layanan Kesehatan Digital pada Puskesmas Payung Sekaki Kecamatan Payung Sekaki Kota Pekanbaru - Syakira Faidila Andri; Dinda Rizky Rahmatilla; Elly Nielwaty (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the implementation of digital health services via the Mobile JKN application at the Payung Sekaki Community Health Center in Pekanbaru City and explores factors affecting service effectiveness, especially complaints about long waiting times. Using a descriptive qualitative approach based on the Mobile Health Acceptance Model by Handayani et al. (2021), the study focuses on five constructs: ease of use, system availability, system responsiveness, health workers’ digital skills, and user trust. The results show that Mobile JKN has significantly simplified administrative processes, accelerated registration, and improved service efficiency at the health center. Effectiveness is supported by factors such as the application’s general ease of use, faster queue data processing, and adequate digital skills among staff. Users also show a high level of trust, though queue time estimation still needs improvement. Despite these benefits, complaints about long waits persist due to patients who register online but still queue manually and misunderstandings between Mobile JKN and e-Puskesmas queue numbers. Late patient arrivals also contribute to delays. Overall, Mobile JKN proves effective in enhancing digital health services, but further optimization is needed through better socialization of service procedures, accurate queue information, and improved system integration to maximize the advantages of digitalization.